Projeto de instalação elétrica de um sistema fotovoltaico Grid-Tie em uma residência para a redução de consumo de energia da concessionária - ARAÚJO, Evanoel Almeida de (2018)
This study is included on the big area of energy efficiency, having as its main focus the production of photovoltaic energy through a system connected to the grid (Grid-Tie). A photovoltaic generation system will be designed to be used in a common residence, currently only fed by the public power grid. The designed system will aim to reduce in the residence, the consumption of electricity from the local utility. Thus, the knowledge of electrical installations of the residence will be necessary, load forecast for this as well as the energy demand, current consumption and expenses arising from the payment of monthly bills for the consumption of the energy delivered by the concessionaire. It will also be necessary a deeper understanding of photovoltaic systems as, therefore, there will be a deeper detailing of each component of the system itself, especially photovoltaic modules, explaining the operating principle of these, types and forms of sizing of them. Regulations of this type of system are exposed as well, showing what is needed to be done on the project to meet them. After the house load parameter being adjusted and further quantities of the system, such as allocation, etc. is exposed at the end of the study a comparison between the energy consumption from de grid before and after the theoretical implementation of the designed system.